Enhancement of air cooling in staggered array of electronic modules by integrating delta winglet vortex generators - S. Chomdee (2018)
This study is to experimentally investigate the heat transfer enhancement by delta winglet vortex generators in air cooling of a staggered array of rectangular electronic modules. The winglet vortex generators are placed in front of 3 × 5 modules with 20° attack angle. Each module has dimensions of 1.8 × 5.4 × 0.6 mm and each one generates heat at 2.5 W. The adiabatic heat transfer coefficients, the thermal wake functions including their correlations for the modules with and without the vortex generators are considered at different values of Reynolds number and the module density. It could be seen that the vortex generators could enhance the adiabatic heat transfer coefficients, reduce the thermal wake functions and the module temperatures significantly. The module temperatures predicted by the superposition of the convective effect due to the module heat generations and the module thermal wakes are fitted very well with the measured data. © 2006 Elsevier Ltd. All rights reserved.